A review of stingless bee plant sources in the Indo‑Malayan region - Yek, Sze Huei; E Alim (International Union for the Study of Social Insects (IUSSI), 2025)
Stingless bees are vital in pollinating crops and wild plants, and their products are valued supplemental nutrient sources to humans. Due to the rise of meliponiculture in the Indo-Malayan region, there is growing interest in understanding stingless bees’ foraging suitability and preferences. This review aimed to identify (1) the common stingless bee species studied, (2) the dominant plant taxa being foraged by stingless bees at diferent habitat types, and (3) the research methodology employed to study plant preference for foraging stingless bees. Twenty-six studies from the Indo-Malayan countries were reviewed. Fabaceae is the most foraged plant family. In general, stingless bees will forage on the most dominant plant species in the habitat. Hence, mixed-type habitats have the highest number of plant species foraged by stingless bees. Stingless bees prefer crops and weed species such as Cocos nucifera and Mimosa pudica. Most countries focus their study on commercial stingless bee species. Our review indicates that stingless bee nutrient forage studies in the Indo-Malayan region can be improved by shifting focus to non-commercial stingless bee species residing in forests, adopting less time-consuming methodology such as plant DNA metabarcoding, and extending nutrient forage studies duration to at least 12 months to account for seasonal variations.